Penyerapan Tenaga Kerja Terhadap Job Analysis Good Manufacturing Practice pada Kelompok Pengolah Hasil Perikanan - Amir, Astaman; Monika, Nova Suryawati (MuJAgri: Musamus Journal of Agribusiness, 2020)
The fishery product processing group is a small industry in Makassar City with 128 groups with 292 tons of production. So that the existence of a small industry or home industry is expected to be able to absorb labor. In the fishery product processing industry will not be separated from Good Manufacturing Practice (GMP). Based on the GMP, the fishery product processing group compiles Job Analysis, namely selection of raw materials for production, handling of raw materials, product processing, selection of auxiliary and chemical ingredients, product packaging, product storage and product distribution. This study aims to analyze the level of employment for GMP job analysis. The study was conducted in Makassar City. The sampling method is non probability sampling, using the Slovin formula with a 10% accuracy limit so that the samples taken were 87 out of 654 people. Data analysis uses a combination of quantitative analysis and qualitative analysis. The results showed that 9% of respondents were tasked with selecting raw materials, 73% of respondents were tasked with handling and processing, 0% of respondents were selecting chemical and auxiliary materials, 10% of respondents were packing, 1% of respondents were storing and 7% were distributing. The highest absorption of labor is handling and processing while the lowest is selection of auxiliary materials and chemicals. Keywords: labor; good manufacturing practice; fishery product processing group